Ecological Impact of Forest Fires and Subsequent Restoration in Chile - Carrasco-Armijo, R (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
This note analyzes the effects forest fires in Chile have on vegetation and subsequent ecological restoration. We analyze why forest fires have been amain factor that affects the environment and causes the ecosystem to deteriorate, leading to loss of native forests, species extinction, damage to the urban population, and others. The data examined are derived from fire hotspots in Chile s central and central-south zones (33°00 S-41°57 S) between 1985 and 2017. We also analyze some key aspects for restoration priorities such as studying affected areas and posterior consequences. Finally, we evaluate actions the country has already taken, and propose further appropriate preventive and restoration measures. © 2018 by the authors.